Derivatives between carbon allotropes and pyrrole derivatives, elastomer mixtures containing them and tires containing such mixtures

Through the adduct of sp2 hybrid carbon allotrope and sulfur-containing pyrrole derivatives, the compatibility and mechanical enhancement of carbon black and elastomer matrix in tire compounds is solved, and low hysteresis and energy dissipation are achieved The reduction is suitable for efficient production of tire rubber.

CN113795480BActive Publication Date: 2025-01-03PIRELLI TYRE SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980096064.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-07
Filing Date
2019-11-05
Publication Date
2025-01-03
Estimated Expiration
2039-11-05

AI Technical Summary

Technical Problem

The prior art has challenges in improving the compatibility and mechanical enhancement effect of carbon black with elastomer matrix in tire compounds, especially while reducing Payne effect and energy dissipation, the industrial development process is complex and the environmental impact is large.

Method used

Adducts between sp2 hybrid carbon allotropes and sulfur atom-containing pyrrole derivatives are used to form stable interactions to improve the dispersion effect and mechanical enhancement performance of carbon black in the elastomer matrix and reduce Payne Effects and energy dissipation.

Benefits of technology

The optimal dispersion and stable interaction between carbon black and elastomeric matrix in tire materials is achieved, reducing Payne effect and energy dissipation, and improving the performance adaptability and environmental friendliness of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113795480B_ABST
    Figure CN113795480B_ABST
Patent Text Reader

Abstract

The present invention relates to sp 2 The invention further relates to a tyre for vehicle wheels comprising at least one structural element comprising a crosslinked elastomeric material obtained by crosslinking such a crosslinkable elastomeric composition.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to the development of novel adducts between pyrrole derivatives containing at least one sulfur and carbon allotropes as components for the production of crosslinked elastomeric materials for vehicle tires and wheels. Prior art

[0002] Carbon black has been used as a reinforcement material for elastomers for over a century.

[0003] The reinforcing effect of carbon black is due to its compatibility with the elastomeric matrix, which is largely composed of hydrocarbon polymers, and at the same time to its insolubility within the elastomeric matrix; to its modulus, which is much greater than that of the elastomeric matrix; to the submicron size of its constituent particles and of the aggregates of these particles; and finally to its so-called "structure".

[0004] The term "structure" is used to indicate that the constituent particles are bonded together by covalent bonds, leaving pores between them. These pores are able to accommodate the polymer chains of the elastomeric matrix, anchoring them and transforming them from a viscous fluid into a reinforcing filler. The greater the amount of empty space, the larger the structure.

[0005] The submicron size and thus high surface area of ​​carbon black, moreover, enable good interactions and extensive interfaces between the reinforcing filler and the polymer chains of the elastomeric matrix, which are essential prerequisites for mechanical reinforcement.

[0006] Carbon black has sp 2 Hybridized carbon allotrope. With sp 2 Other carbon allotropes that are hybridized are, for example, fullerenes, carbon nanotubes, graphene and nanographites with several stacked graphene layers. These allotropes have nanometer dimensions and, for the most part, are endowed with high aspect ratios, and thus high surface areas, and are therefore able to establish high interfacial areas with the elastomer matrix. They are therefore potentially ideal fillers for giving the elastomer matrix major mechanical reinforcement.

[0007] Mechanical reinforcement was evaluated at both low and high deformations.

[0008] Reinforcement at low deformations depends mainly on the surface area of ​​the reinforcing filler. The high surface area of ​​the reinforcing filler promotes extensive interactions with the polymer chains and with other particles in the filler, essentially based on non-bonded forces. By applying energy and progressively increasing the amplitude of deformation, the reinforcement based on non-bonded interactions ceases to exist and the viscoelastic modulus decreases, accompanied by energy dissipation. This phenomenon is called the Payne effect.

[0009] In contrast, the reinforcement at high deformations is due to the stabilizing interaction between the polymer matrix and the filler, which in the case of conventional reinforcing fillers such as carbon black is due to the structure of the filler, i.e. the pores between the elementary particles of the filler itself.

[0010] The main application of such elastomeric compositions is in tire compounds, for which it is desirable to obtain a reinforcement consistent with an increased deformation, ie a reduced Payne effect, with the aim of minimizing energy dissipation which would otherwise lead to greater fuel consumption and environmental impact.

[0011] A reduced Payne effect can be obtained by optimizing the dispersion of reinforcing fillers, such as carbon black, in the elastomeric matrix, separating the aggregates and / or elementary particles therefrom and covering them with an elastomeric layer. Various possibilities for obtaining this optimization are known in the art, such as: (i) mixing the allotrope with the elastomeric matrix by means of mechanical energy, (ii) dissolving the elastomeric matrix in a solvent and subsequent mixing, (iii) chemically modifying the allotrope with the aim of obtaining a solubility parameter as similar as possible to that of the matrix, or with the aim of making the allotrope itself dispersible in an aqueous latex of the elastomer constituting the matrix.

[0012] The use of mechanical energy is currently the most common approach at the industrial level. However, this presents some disadvantages: high mixing energy leads to degradation of the polymer matrix and / or reinforcing fillers (see, for example, Macromol. Mater. Eng. 2012, 298, 241-251), and the thermodynamic incompatibility of carbon allotropes with elastomers leads to reaggregation of fillers in a timely manner (see, for example, Rubber Chemistry and Technology 2014, 87, 2, 197-218).

[0013] On the other hand, regarding the possibility of obtaining a mixture in a solvent, the first attempts reported in the prior art generally utilize aromatic solvents, such as toluene (see, for example, Journal of Applied Polymer Science 2012, 125, E76-E84). This, together with the complexity of the process, makes the possibility of industrial development difficult.

[0014] Therefore, in recent years, research has focused on chemically modifying reinforcing fillers, such as carbon black, with the goal of increasing their compatibility with the elastomeric matrix.

[0015] Matos et al. (Carbon 2012, 50, 4685-4695) reported the preparation of a composite material comprising natural rubber and carbon nanotubes containing magnetic material in their cavities and treated with sodium dodecyl sulfate (SDS). The process of forming the adduct is complicated and the adduct is only compatible with polymer latex. In addition, although carbon allotropes can make it more compatible with polymers, they cannot form any chemical bonds with them.

[0016] EP3209604B1 and WO2018 / 087685A1 under the name of the applicant describe sp 2 Adducts between hybridized carbon allotropes and pyrrole derivatives, which can modify the compatibility of carbon allotropes with a wide range of solid and liquid matrices. The inventors also describe the preparation of stable dispersions of such adducts in water (see also RSC Adv., 2015, 5(99), 81142-81152) and in latex of natural rubber (see also Rubber Chem. Technol., 2017, 90(2), 285-307).

[0017] The prior art describes other attempts to modify the chemical and physical properties of reinforcing fillers with the aim of increasing their compatibility with the elastomeric matrix.

[0018] US 2015 / 0191579 A1 describes carbon black aggregates having inorganic polysulfides adsorbed on their surfaces, elastomeric compositions containing them and tires containing such elastomeric compositions.

[0019] The reduction of the Payne effect and thus of the energy dissipation is one of the main objectives in the production of tyres and in particular of tread compounds, which represent, in quantitative and qualitative terms, the main component of the tyre itself. SUMMARY OF THE INVENTION

[0021] Applicants have addressed the need to obtain an elastomeric composition comprising a commercially available elastomer and a sp 2 Hybridized carbon allotropes characterized by optimal dispersion and stabilizing interactions between the carbon allotropes and polymer chains of the elastomeric matrix, and wherein the carbon allotropes maintain their sp 2 The properties remain basically unchanged.

[0022] The Applicant has also addressed the need to obtain such an elastomeric composition with reduced environmental impact by means of simple technology and using standard solid-state mixing techniques used in the tire industry.

[0023] Surprisingly, the applicant has found that sp 2The adducts between hybrid carbon allotropes and pyrrole derivatives containing one or more sulfur atoms are dispersed more effectively than expected within the elastomeric matrix, forming stable interactions with these. The elastomeric compositions thus obtained exhibit low hysteresis and reduced Payne effect, resulting in reduced energy dissipation, and are therefore particularly suitable as rubber compounds for tires, especially tread bands.

[0024] The present invention therefore relates to sp 2 An adduct between a hybridized carbon allotrope and a pyrrole derivative, wherein the pyrrole derivative is represented by formula (1):

[0025]

[0026] in

[0027] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl;

[0028] Dashed lines (a') and (b') independently represent a double bond or a single bond; and

[0029] W, Y and Z are independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl, and the following chemical formula (II)-(V)

[0030]

[0031] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , and R 21 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0032] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0033] and wherein m is an integer from 1 to 4, and n, o, p, q, r and s are independently integers from 1 to 12;

[0034] and among them

[0035] When both the dashed lines (a') and (b') represent double bonds, the formula (1) is represented by the formula (1a), wherein R1-R4 and W, Y, and Z have the meanings described above,

[0036]

[0037] and provided that at least one of W, Y, and Z is represented by one of the above formulae (II)-(III);

[0038] or

[0039] When only the dashed line (b') represents a double bond, then Y is hydrogen, W is a -CH2-S- group, which together with the carbon at position "a" forms a 5-membered ring, and formula (1) is represented by formula (1b), wherein R1-R4 and Z have the meanings described above

[0040]

[0041] or,

[0042] When both dashed lines represent single bonds, then both Y and W are -CH2-S- groups, and they each form a 5-membered ring together with the carbon at positions "a" and "b", and formula (1) is represented by formula (1c), wherein R1-R4 and Z have the meanings described above

[0043]

[0044] A second aspect of the present invention relates to obtaining the sp described above 2A process for producing an adduct between a hybridized carbon allotrope and a pyrrole derivative containing at least one sulfur atom, wherein the process comprises the steps of:

[0045] a) forming at least one compound of formula (1) described above and at least one sp 2 mixtures of hybridized carbon allotropes; and

[0046] b) supplying energy to the resulting mixture to cause an interaction between the functional group of the compound of formula (1) and the allotrope.

[0047] The third aspect of the present invention uses the sp described above 2 The use of the adduct between a hybridized carbon allotrope and a pyrrole derivative containing at least one sulfur atom for preparing a composition, preferably an elastomeric composition, is indicated.

[0048] A fourth aspect of the present invention is represented by a crosslinkable elastomeric composition comprising a crosslinkable elastomeric polymer according to the present invention. 2 Adducts between hybridized carbon allotropes and pyrrole derivatives containing at least one sulfur atom.

[0049] A fifth aspect of the invention is represented by a tyre for vehicle wheels, said tyre comprising at least one structural element comprising a crosslinked elastomeric material obtained by crosslinking the crosslinkable elastomeric composition according to the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] The description is set forth herein with reference to the accompanying drawings, which are provided by way of example only and are not limiting of the present invention.

[0052] Figure 1 : summarizes the profile of a transverse half-section of a motor vehicle tire containing, in one or more components, an elastomeric composition according to the invention.

[0053] Figure 2 : is a graph showing the vulcanization curves of the elastomeric compositions of Examples 9-13, wherein time (min) is shown on the x-axis and the torque required to rotate the rheometer disk in the material during the vulcanization stage is shown on the y-axis. This torque is represented by S' and the unit of measurement is dNm.

[0054] Figure 3 : is a graph showing the change in G′ (y-axis) versus the deformation amplitude (x-axis) of the elastomer compositions of Examples 9-13;

[0055] Figure 4 : is a graph showing the change in tan δ (y-axis) versus the deformation amplitude (x-axis) of the elastomer compositions of Examples 9-13;

[0056] Figure 5 : is a graph showing the dependence of the tan δ value (y-axis) of the elastomer compositions of Examples 9-10 and 12-13 on the temperature (x-axis);

[0057] Figure 6 : is a graph showing the change in stress (y-axis) versus strain (x-axis) for the elastomeric compositions of Examples 9-10 and 12-13;

[0058] Figure 7 : is a graph showing the vulcanization curves of the elastomeric compositions of Examples 14-17, wherein time (min) is shown on the x-axis and the torque required to rotate the rheometer disk in the material during the vulcanization step is shown on the y-axis. This torque is denoted S' and the unit of measurement is dNm.

[0059] Figure 8 : is a graph showing the change in tan δ (y-axis) versus deformation amplitude (x-axis) for the elastomer compositions of Examples 14-17; and

[0060] Fig. 9 : is a graph showing the change in stress (y-axis) versus strain (x-axis) for the elastomer compositions of Examples 14-17. DETAILED DESCRIPTION OF THE INVENTION

[0062] definition

[0063] In the present specification, the term "pyrrole derivatives" is understood to mean compounds of formula (1) as defined above and in the appended claims. In the present invention, pyrrole derivatives of formula 1 are also defined as pyrrole derivatives containing at least one sulfur atom.

[0064] According to the invention, the term "adduct" is understood to mean a compound obtained by means of an addition reaction; more specifically, the term adduct denotes those specific addition compounds which in some way retain their independence through the components being bonded more or less loosely, i.e. by means of covalent bonds or by means of more active intermolecular interactions. In particular, according to the invention, the term "adduct" is used to mean a compound consisting of a pyrrole derivative containing at least one sulfur atom and a sp 2 Interactions between hybridized carbon allotropes, adducts obtained through covalent or non-covalent bonds.

[0065] According to the present invention, the terms "carbon allotrope" and "carbon-based filler" may be used interchangeably and / or both may be represented by the abbreviation CA.

[0066] For the purpose of this specification and the following claims, the term "phr" (parts per hundred parts of rubber) denotes the parts by weight of a defined component of the elastomeric composition relative to 100 parts by weight of the elastomeric polymer.

[0067] The term "graphene" is generally used to refer to a structure containing one or at most several layers of carbon atoms organized in hexagonal aromatic rings. According to the guidelines established by the International Organization for Standardization (ISO), according to the definition established by ISO (Organization for Standardization (ISO) Nanotechnologies-Vocabulary-Part 13: Graphene and Related Two-Dimensional (2D) Materials, BSI Standards Publication, London, UK 2017), the terms "bilayer graphene" and "several layers of graphene" refer to graphene with 2 layers and graphene with 3 to 10 layers of carbon atoms organized in hexagonal aromatic rings, respectively. According to this guideline, in the case of more than 10 layers, the resulting material typically has graphitic characteristics (especially electrical properties).

[0068] Detailed description

[0069] The first aspect of the present invention is sp 2 An adduct between a hybridized carbon allotrope and a pyrrole derivative, wherein the pyrrole derivative is represented by formula (1):

[0070]

[0071] in

[0072] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl;

[0073] Dashed lines (a') and (b') independently represent a double bond or a single bond; and

[0074] W, Y and Z are independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl, and the following defined formula (II)-(V)

[0075]

[0076] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , and R 21 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0077] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0078] and wherein m is an integer from 1 to 4, and n, o, p, q, r and s are independently integers from 1 to 12;

[0079] and among them

[0080] When both dashed lines (a') and (b') represent double bonds, the formula (1) is represented by the formula (1a), wherein R1-R4 and W, Y, and Z have the meanings described above,

[0081]

[0082] and provided that at least one of W, Y, and Z is represented by one of the above formulae (II)-(III);

[0083] or

[0084] When only the dashed line (b') represents a double bond, then Y is hydrogen, W is a -CH2-S- group which together with the carbon at position "a" forms a 5-membered ring, and formula (1) is represented by formula (1b), wherein R1-R4 and Z have the meanings described above

[0085]

[0086] or,

[0087] When both dashed lines represent single bonds, then both Y and W are -CH2-S- groups, and they each form a 5-membered ring together with the carbon at positions "a" and "b", and formula (1) is represented by formula (1c), wherein R1-R4 and Z have the meanings described above

[0088]

[0089] By convention, in Formula 1b, the dashed line (b') in Formula (1) represents a double bond, and the possibility that the dashed line (a') in Formula (1) represents a double bond is also considered.

[0090] Preferably, the sp used to prepare the adduct of the present invention 2 The hybrid carbon allotrope is selected from carbon black, graphene (possibly graphene with 2 layers (bilayer graphene) or graphene with several layers (e.g. 3 to 10; several layers of graphene)), graphite, in particular high surface area graphite, single-walled or multi-walled carbon nanotubes, carbon nanotubes with longitudinal or helical extension, nanocones, nanohorns, nanorings, other structures of nanotubes or graphene structures (e.g. graphene clusters, graphene ribbons, 2D or 3D networks of graphene or nanotubes, graphite crystals), fullerenes.

[0091] More preferably, sp 2 The hybrid carbon allotrope is selected from carbon black, fullerenes, single-walled or multi-walled carbon nanotubes with 2 layers (bilayer graphene), graphene with several layers (3 to 10; several-layer graphene), graphite, especially high surface area graphite, or mixtures thereof.

[0092] Still more preferably, sp 2 The hybrid carbon allotrope is selected from carbon black, graphene with 2 layers (bilayer graphene), graphene with several layers (3 to 10; several-layer graphene), graphite (e.g., with a number of graphene layers between 10 and 10,000), in particular high surface area graphite, single-walled or multi-walled carbon nanotubes or mixtures thereof.

[0093] In a particularly preferred embodiment, sp 2 Hybrid carbon allotropes are carbon black alone or mixed with one or more carbon allotropes.

[0094] In another particularly preferred embodiment, sp 2 Hybridized carbon allotropes are high surface area graphites alone or mixed with other carbon allotropes.

[0095] In one embodiment, sp 2 The hybridized carbon allotrope contains a functional group selected from:

[0096] - oxygen-containing functional groups, preferably hydroxyl or epoxy groups;

[0097] - a carbonyl-containing functional group, preferably an aldehyde group, a ketone group, or a carboxylic acid group;

[0098] - a nitrogen atom-containing functional group, preferably an amine group, an amide group, a nitrile group, a diazonium salt or an imine group;

[0099] - a sulfur atom-containing functional group, preferably a sulfide group, a disulfide group, a thiol group, a sulfone group, a sulfinic acid group and a sulfonic acid group.

[0100] According to one embodiment of the present invention, the pyrrole derivative used to prepare the adduct is represented by formula (1a):

[0101]

[0102] in

[0103] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl;

[0104] W, Y and Z are independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl, and the following formula (II)-(V)

[0105]

[0106] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , and R 21 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0107] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0108] and wherein m is an integer from 1 to 4, and n, o, p, q, r and s are each independently an integer from 1 to 12;

[0109] Provided that at least one of W, Y and Z is represented by one of the above formulae (II) to (III).

[0110] Preferably, according to this embodiment, the pyrrole derivative used to prepare the adduct is represented by formula (1a):

[0111]

[0112] in

[0113] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl;

[0114] W is selected from: hydrogen, straight or branched C1-C 18 Alkyl and straight or branched C2-C 18 alkenyl or alkynyl; and

[0115] Y and Z are independently represented by one of the following formulae (II) to (III):

[0116]

[0117] Among them, R5, R6, R7, R8, R9, R10 , R 11 , R 12 , and R 13 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkylcarboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0118] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0119] and wherein m is an integer from 1 to 4, and n, o, p are integers from 1 to 12 independently of each other.

[0120] Alternatively, the pyrrole derivative used to prepare the adduct is represented by formula (1a).

[0121]

[0122] in

[0123] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl;

[0124] W and Y are independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl; and

[0125] Z is represented by one of the following formulas (II) to (III):

[0126]

[0127] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , and R 13 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0128] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0129] and wherein m is an integer from 1 to 4, and n, o, p are integers from 1 to 12 independently of each other.

[0130] In a particularly preferred embodiment, the pyrrole derivative used to prepare the adduct is represented by formula (1a):

[0131]

[0132] in

[0133] R1, R2, R3, and R4 are independently selected from: hydrogen and straight or branched C1-C3 alkyl;

[0134] W and Y are independently selected from: hydrogen and straight or branched C1-C3 alkyl; and

[0135] Z is represented by one of the following formulas (II) to (III):

[0136]

[0137] Among them, R5, R6, R8, R9, R 10 , and R 11 represented by hydrogen or a straight or branched C1-C3 alkyl group; and

[0138] R7, R 12 and R 13Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, with a straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 acyl-alkenyl, and acyl-aryl, wherein the aryl group is optionally substituted with one or more carboxyl groups;

[0139] or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups;

[0140] and wherein m is 1, and n, o, p are integers from 1 to 4 independently of each other.

[0141] According to an alternative embodiment of the present invention, the pyrrole derivative used to prepare the adduct is represented by formula (1b):

[0142]

[0143] in

[0144] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl; and

[0145] Z is selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl, and the following formula (II)-(V)

[0146]

[0147] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , and R 21 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0148] or R 12 and R 13 Together they form a pyrrole ring;

[0149] and wherein m is an integer from 1 to 4, and n, o, p, q, r and s are independently integers from 1 to 12.

[0150] Preferably, according to this alternative embodiment, the pyrrole derivative used to prepare the adduct is represented by formula (1b):

[0151]

[0152] in

[0153] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl; and

[0154] Z is selected from: hydrogen, straight or branched C1-C 18 Alkyl and straight or branched C2-C 18 Alkenyl or alkynyl.

[0155] According to a further alternative embodiment of the present invention, the pyrrole derivative used to prepare the adduct is represented by formula (1c):

[0156]

[0157] in

[0158] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl; and

[0159] Z is selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 alkenyl or alkynyl, and the following formula (II)-(V)

[0160]

[0161] Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , and R 21 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, linear or branched C2-C 18 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, heteroaryl, carboxyl, with straight or branched C1-C 18 Alkyl acyl-alkyl, with a straight or branched C2-C 18 Acyl-alkenyl or acyl-alkynyl, acyl-aryl, acyl-heteroaryl, and acyl-amine of alkenyl and alkynyl, wherein the aryl and heteroaryl are optionally substituted with one or more groups selected from the group consisting of C1-C3 alkyl, carboxyl, and acyl-alkyl having a C1-C3 alkyl group;

[0162] or R 12 and R 13 Together they form a pyrrole ring;

[0163] and wherein m is an integer from 1 to 4, and n, o, p, q, r and s are independently integers from 1 to 12.

[0164] Preferably, according to this alternative embodiment, the pyrrole derivative used to prepare the adduct is represented by formula (1c):

[0165]

[0166] in

[0167] R1, R2, R3, and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl; and

[0168] Z is selected from: hydrogen, straight or branched C1-C 18 Alkyl and straight or branched C2-C 18 Alkenyl or alkynyl.

[0169] According to a particularly preferred embodiment, the pyrrole derivative of formula (1a) is selected from:

[0170] -2-(2,5-dimethyl-1H-pyrrol-1-yl)ethane-1-thiol,

[0171] -1,2-bis(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl) disulfide,

[0172] -S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)ethanethiol,

[0173] -S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)prop-2-enethioate,

[0174] -S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)2-methylprop-2-enethiol,

[0175] -2-((2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)disulfanyl)-N,N-dimethylethane-1-amine,

[0176] -S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)octadecylthiosulfate; and

[0177] -2-(((2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)thio)carbonyl)benzoic acid,

[0178] and mixtures thereof.

[0179] The pyrrole derivatives used to prepare the adducts according to the present invention can be prepared according to methods known in the art (see, for example, Barbera, Vincenzina et al., "Facile and sustainable functionalization of graphene layers with pyrrole compounds." Pure and Applied Chemistry 90.2 (2018): 253-270).

[0180] Briefly, a suitable primary amine is reacted with a diketone of the following general formula:

[0181]

[0182] Wherein R1, R2, R3, R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, linear or branched C2-C 22 Alkenyl or alkynyl, aryl, straight or branched C1-C 22 Alkyl-aryl, linear or branched C2-C 22 Alkenyl-aryl, straight or branched C2-C 22 Alkynyl-aryl, and heteroaryl.

[0183] Particularly preferred are pyrrole derivatives containing at least one sulfur atom of formula 1a) represented above and sp 2 adducts formed between hybridized carbon allotropes, the sp 2 The hybrid carbon allotrope is selected from the group consisting of carbon black, fullerenes, single-walled or multi-walled carbon nanotubes, graphene with 2 layers (bilayer graphene), graphene with several layers (e.g. 3 to 10; several-layer graphene), graphite (e.g. with graphene layers with a number of layers ranging from 10 to 10,000), and single-walled or multi-walled carbon nanotubes, in particular high surface area graphite and mixtures thereof.

[0184] More preferably, sp 2 The adduct between the hybridized carbon allotrope and the pyrrole derivative according to the present invention is selected from the adduct between carbon black and the pyrrole derivative of formula 1a), the adduct between high surface area graphite and the pyrrole derivative of formula 1a), and the adduct between single-walled or multi-walled carbon nanotubes and the pyrrole derivative of formula 1a).

[0185] Still more preferably, the adduct according to the present invention is selected from carbon black, high surface area graphite, graphene with 2 layers (bilayer graphene), graphene with several layers (e.g. 3 to 10; several layers of graphene), and sp in single-walled or multi-walled carbon nanotubes. 2Hybridized carbon allotrope, adducts with pyrrole derivatives of formula 1a) selected from the group consisting of 2-(2,5-dimethyl-1H-pyrrol-1-yl)ethane-1-thiol, 1,2-bis(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl) disulfide, S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethylethanethiosulfate, S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethylprop-2-enethiosulfate ester, S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)2-methylprop-2-enethiosulfate, 2-((2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)disulfanyl)-N,N-dimethylethane-1-amine, S-(2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyloctadecylthiosulfate; and 2-(((2-(2,5-dimethyl-1H-pyrrol-1-yl)ethyl)thio)carbonyl)benzoic acid.

[0186] Preferably, the adduct is characterized in that the weight ratio between the allotrope and the pyrrole derivative is comprised between 100:1 and 1:10, still more preferably between 100:1 and 1:1.

[0187] Carbon allotropes, due to the fact that they are more or less reactive aromatic systems, can form various types of intermolecular interactions, both of the covalent type and by means of more reactive intermolecular interactions.

[0188] Without being bound by any theory, the following two types of interactions can be postulated in the adduct formation reaction:

[0189] (i) π-π interaction: a kind of interaction that can exist between two molecules with π electrons and thus sp 2 The interaction is between a pair of π electrons and a σ orbital, or between a σ orbital and an electron of a π orbital, or between two π orbitals. This type of adduct is also called a "π complex" and is characterized by the so-called stacking, i.e. the stacking arrangement of the aromatic molecules.

[0190] (ii) Covalent bonding between the compound of formula (1) and the carbon allotrope by means of reactions typical of polycyclic aromatic systems, such as 1,3-dipolar cycloaddition, Diels-Alder reaction.

[0191] The formation of adducts may also occur by means of interactions between functional groups in the pyrrole derivatives of formula (1) and functional groups possibly present on the carbon allotrope. These interactions may be of an intermolecular nature, such as hydrogen bonds and dipole interactions, or of a covalent nature, such as esterification by reaction with acidic groups.

[0192] The realization of this interaction (whether of an intermolecular or covalent nature) can also be carried out solely by input of energy (for example mechanical or thermal energy, or by irradiation with photons), without the use of solvents.

[0193] A second aspect of the invention is therefore to obtain a 2 A process for producing an adduct between a hybridized carbon allotrope and a pyrrole derivative containing at least one sulfur atom, the process comprising the steps of:

[0194] a) forming at least one compound of formula (1) and at least one sp 2 mixtures of hybridized carbon allotropes; and

[0195] b) supplying energy to the resulting mixture to effect interaction between the compound of formula (1) and the allotrope, thereby obtaining sp 2 Adducts between hybridized carbon allotropes and pyrrole derivatives.

[0196] Optionally, the adduct is separated from the non-interacting carbon allotrope and / or pyrrole derivative using methods known to those skilled in the art.

[0197] The energy transfer of step b) of the process according to the invention is carried out in order to improve the interaction between the compound of formula (1) and the carbon allotrope. In the absence of energy transfer, this interaction would be weaker and could lead to a partial release of the compound of formula (1) from the carbon allotrope, especially if the adduct is in an environment of a polar nature.

[0198] The form of energy that can be transferred to the composition to allow adduct formation is: mechanical energy; thermal energy; photons, or a combination of two or more of these forms of energy.

[0199] Mechanical Energy

[0200] The mechanical treatment may consist, for example, of placing the powder obtained (allotrope / compound of formula (I)) in a ball mill, for example containing a tank equipped with stainless steel balls. Once closed, the tank is placed in a planetary mixer and rotated at a speed of 200 to 500 rpm for a period of 1 to 360 minutes. The powder is then immediately poured out.

[0201] Mechanical treatment is used to promote both the separation of the carbon allotropes into their elementary components (e.g. exfoliation in the case of graphite) and to favour the relative dispersion of the allotropes and the compound of formula (I), so as to obtain a better distribution of the compound of formula (I) on the allotropes and to induce the formation of more stable interactions.

[0202] Thermal Energy

[0203] The heat treatment may consist, for example, of placing the resulting powder (carbon allotrope / compound of formula (I)) in a reaction flask or sealed flask equipped with a condenser. After placing the reactor on a heating table, the reaction is carried out at a temperature of 130 to 180° C. The heating is maintained for a period of 15 to 360 minutes.

[0204] Photon

[0205] The photon treatment may consist, for example, of placing the resulting powder (carbon allotrope / compound of formula (I)) in a laboratory crystallizer to form a thin layer or placing the powder in a sealed quartz vial. The reaction vessel is placed in a closed chamber equipped with a 254 nm low-pressure mercury lamp (or using a reactor equipped with the same type of reactor). After being placed in a reactor, the mixture is irradiated for a time variable from 30 to 180 minutes. After this time, the mixture is transferred and analyzed.

[0206] In one embodiment, the sp according to the present invention is obtained 2 The method for preparing an adduct between a hybridized carbon allotrope and a pyrrole derivative comprises the following steps:

[0207] i) obtaining a solution of at least one compound of formula (1) in a polar protic or aprotic solvent selected from the group consisting of water, alcohols, carbonyl solvents such as acetone, esters such as ethyl acetate, dimethyl sulfoxide, acetonitrile, ethers or mixtures thereof;

[0208] ii) obtaining a suspension of the carbon allotrope in the polar protic or aprotic solvent used to prepare the solution in step i);

[0209] iii) mixing the solution and the suspension by mechanical or magnetic stirring or by ultrasonic treatment;

[0210] iv) removing the solvent from the mixture obtained in step iii); and

[0211] v) providing thermal energy and / or mechanical energy and / or energy of irradiation with photons to the mixture obtained in step iv) in the presence of air or oxygen.

[0212] Preferably, the thermal energy is supplied at a temperature of 50 to 180° C. for 15 to 360 minutes.

[0213] Preferably, the mechanical energy is supplied for a period of 1 to 360 minutes.

[0214] Preferably, the energy irradiated with photons is provided at a wavelength of 200 to 380 nm for a period of 30 to 180 minutes.

[0215] The process according to this embodiment makes it possible to obtain a homogeneous dispersion of carbon allotropes and of at least one compound of formula (1), and therefore of the compound of formula (1) within the carbon-based filler.

[0216] Preferably, the solvent of step i) is an eco-compatible solvent, such as water.

[0217] Alternatively, the preparation of the adduct can be carried out without the previous preparation of a mixture and / or suspension according to the aforementioned steps i) and ii), simply by mixing the two components and supplying energy.

[0218] Removal of the solvent from the resulting mixture (step iv) may occur by any suitable method for removing the solvent, such as vacuum evaporation, spray drying, and the like.

[0219] A further aspect of the present invention is represented by a crosslinkable elastomeric composition comprising a crosslinkable elastomeric composition as described above, according to the present invention. 2 Adducts between hybridized carbon allotropes and pyrrole derivatives having at least one sulfur atom.

[0220] The elastomeric composition according to the present invention comprises at least one unsaturated elastomer selected from the group consisting of poly(1,4-cis-isoprene) (either natural rubber or synthetic polymer), poly(3,4-isoprene), poly(butadiene) (especially poly(butadiene) with a high 1,4-cis unit content), isoprene / isobutylene copolymers, halogenated isoprene / isobutylene copolymers, such as halogenated butyl rubbers, especially chlorinated butyl rubber and brominated butyl rubber, 1,3-butadiene / acrylonitrile copolymers, styrene / 1,3-butadiene copolymers, styrene / isoprene / 1,3-butadiene copolymers, styrene / 1,3-butadiene / acrylonitrile copolymers, or mixtures thereof.

[0221] The elastomeric composition according to the invention may further contain at least one elastomer of one or more monoolefins. The monoolefins may be chosen from ethylene and 1-olefins having 3 to 12 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, or mixtures of these monoolefins.

[0222] The monoolefin elastomer(s) may contain a diene, which generally has from 4 to 20 carbon atoms and is preferably selected from 1,3-butadiene, isoprene, 1,4-hexadiene, 1,4-cyclohexadiene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, vinyl norbornene or mixtures of these dienes. The diene may optionally be halogenated.

[0223] Among these elastomers of monoolefin(s), the following are preferred: ethylene / propylene copolymers (EPR) or ethylene / propylene / diene copolymers (EPDM), and poly(isobutylene).

[0224] The elastomeric composition may further contain unsaturated, diene or non-diene monomer-based elastomers, which are functionalized by reaction with suitable end-capping or coupling agents. In particular, diene elastomeric polymers may be obtained by anionic polymerization promoted by organometallic initiators (especially alkyl lithium) and end-capped by reaction with suitable end-capping or coupling agents such as epoxides, carbonyl compounds such as substituted or unsubstituted cyclohexanones and benzophenones, imines, carbodiimides, alkyltin halides, alkoxysilanes or aryloxysilanes.

[0225] Preferably, the crosslinkable elastomeric composition contains an amount comprised between 5 and 100 phr, more preferably between 10 and 80 phr of the sp according to the invention. 2 Adducts between hybridized carbon allotropes and pyrrole derivatives.

[0226] According to a preferred embodiment, the elastomeric composition also contains a further reinforcing filler selected from carbon black, silica, phyllosilicates, mixed oxides of aluminum and magnesium having a layered structure, aluminum oxide and aluminosilicates.

[0227] Particularly preferred is amorphous silica, which may be of natural origin, such as diatomaceous earth, or synthetic, such as precipitated silica, silica gel, fumed silica, or silica that has undergone a surface treatment.

[0228] Preferably, in the elastomeric composition according to the invention, the total amount of reinforcing fillers, understood as meaning the sum of the amounts of adduct according to the invention and further reinforcing fillers, comprises 20 to 150 phr, more preferably 40 to 80 phr.

[0229] Advantageously, the crosslinkable elastomeric composition contains a vulcanizing agent and is vulcanized according to known techniques, in particular using a sulfur-based vulcanization system commonly used for diene elastomeric polymers. For this purpose, in the material, after one or more thermomechanical treatments, a sulfur-based vulcanizing agent is incorporated together with a vulcanization accelerator. In the final treatment step, the temperature is generally maintained below 120° C. and preferably below 100° C., so as to avoid any undesired pre-crosslinking phenomena.

[0230] Preferably, the vulcanizing agent comprises a sulfur-based vulcanization system comprising sulfur or sulfur-containing molecules (sulfur donors), and vulcanization accelerators and / or activators known in the art.

[0231] Particularly effective activators are zinc compounds, and in particular ZnO, ZnCO3 and zinc salts of saturated or unsaturated fatty acids containing 8 to 18 carbon atoms, such as zinc stearate, which are preferably formed in situ in the elastomeric composition from ZnO and fatty acids, or mixtures thereof.

[0232] Commonly used accelerators may be selected from dithiocarbamates, guanidines, thioureas, thiazoles, sulfenamides, thiurams, amines and xanthates or mixtures thereof.

[0233] Preferred vulcanizing agents are, for example, stearic acid, ZnO, 6PPD (1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine), TBBS (N-tert-butyl-2-benzothiazolylsulfenamide), and sulfur or mixtures thereof.

[0234] According to a preferred embodiment, said crosslinkable elastomeric composition contains a vulcanizing agent in an amount greater than or equal to about 1 phr, preferably greater than or equal to about 2 phr.

[0235] Preferably, the amount of curing agent used is less than or equal to about 7.5 phr, preferably less than or equal to about 7.5 phr.

[0236] Advantageously, sulfur is present in an amount between about 0.5 phr and about 6.5 phr.

[0237] The elastomeric composition may contain other conventional additives, which are selected based on the specific application for which the composition is intended. For example, antioxidants, anti-aging agents, plasticizers, adhesives, anti-ozonants, modifiers, or mixtures thereof may be added to the material.

[0238] In particular, for the purpose of improving workability, a plasticizer generally selected from mineral oils, vegetable oils, synthetic oils or mixtures thereof, such as aromatic oils, naphthenic oils, phthalates, soybean oils or mixtures thereof, may be added to the elastomer composition. The amount of plasticizer generally ranges from 0 phr to about 70 phr, preferably from about 5 phr to about 30 phr.

[0239] The invention can be prepared by mixing the polymer components together with the sp 2 The elastomeric composition is prepared by mixing the adducts between the hybrid carbon allotropes and the pyrrole derivatives, and other reinforcing fillers and possibly other additives. It is possible to use, for example, an open mixer of the "open mill" type and / or an internal mixer with tangential rotors. and / or an internal mixer with intermeshing rotors TM ), and / or in Ko-Kneader TM The mixing is carried out in a continuous mixer of a twin-screw or multi-screw type and / or a planetary type.

[0240] The components of the elastomeric composition are not usually all introduced into the mixer at the same time, but are typically added sequentially. In particular, vulcanization additives, such as vulcanizing agents and possibly accelerators and retarders are usually added in a downstream step with respect to the incorporation and processing of all other components.

[0241] The individual components of the elastomeric composition do not always remain unchanged or individually traceable in the vulcanizable or final vulcanized elastomeric composition in that they can be completely or partially transformed by interaction with other components, by the influence of heat and / or mechanical processing. The term "elastomeric composition" is here to be understood as comprising all the components added in the preparation of the elastomeric mix, independently of the fact that these may in fact all be present simultaneously, that they may be introduced sequentially or that they may then be traceable within the elastomeric mix or within the final tire.

[0242] A further aspect of the invention is represented by a tyre for vehicle wheels comprising at least one structural element comprising a crosslinked elastomeric material obtained by crosslinking the crosslinkable elastomeric composition according to the invention.

[0243] In particular, said tyre comprises at least one carcass structure having opposite lateral edges associated with respective annular reinforcing structures, a belt structure applied in a radially external position with respect to said carcass structure, a tread band applied in a radially external position with respect to said carcass structure, and a pair of sidewalls applied laterally on opposite sides with respect to said carcass structure.

[0244] Advantageously, said structural element is chosen from the group consisting of a tread band, sidewalls, sidewall inserts, layers of elastomeric material radially internal to said tread band, such as cushioning rubbers and mini sidewalls, filler strips, and textile and metal rubber coatings. In a particularly preferred embodiment, the structural element is a tread band.

[0245] Such a structural element, in particular a tread band, may advantageously be prepared using an elastomeric composition comprising a sp 2 Adducts between hybrid carbon allotropes and pyrrole derivatives are characterized by low hysteresis and reduced Payne effect, resulting in significant advantages in terms of road holding and general tire performance, such as resistance to deformation due to, for example, elevated temperatures.

[0246] In addition, it can be proved that sp 2 The aforementioned elastomeric composition of the adduct of the hybrid carbon allotrope and the pyrrole derivative has electrical conductivity, which contributes to the creation of an electrically conductive path between the rim and the ground.

[0247] The tire of the invention can be used on vehicles having two, three or four tires, or on heavy vehicles, or on light transport vehicles.

[0248] The tire according to the invention can be used in summer or winter or in all seasons.

[0249] The tire according to the invention can be manufactured according to a method comprising the following steps:

[0250] - Building a green tire assembly on at least one forming drum;

[0251] - Shaping, molding and vulcanizing tires;

[0252] At least one component of the green tire contains the vulcanizable elastomeric composition described above.

[0253] The term "green" is generally used to refer to a material, composition, component or tire that has not yet been cured.

[0254] The tyre can be finished by assembling the corresponding semi-finished products on a moulding drum (not shown) with the aid of at least one assembling device.

[0255] At least a part of the components intended to form the tyre carcass structure may be constructed and / or assembled on a forming drum. More particularly, the forming drum is prepared to receive first the liner, if any, then the carcass structure and the wear strip. Then, means not shown coaxially engage one of the annular anchoring structures around each end edge, place the outer sleeve containing the belt structure and the tread band in a position coaxially centred on the cylindrical carcass sleeve and shape the carcass sleeve according to the bellmouth configuration by means of radial expansion of the carcass structure, for example causing it to be applied against the radially inner surface of the outer sleeve.

[0256] After the green tire has been manufactured, a molding and vulcanization process is carried out in order to stabilize the structure of the tire by crosslinking the elastomeric mixture and also to emboss the desired tread design on the tread band and possible visible graphic symbols on the sidewalls.

[0257] Figure 1 A radial half-section of a tyre for a vehicle wheel according to the invention is illustrated.

[0258] exist Figure 1 In the diagram, "a" represents the axial direction and "X" represents the radial direction, and in particular, XX represents the curve of the equatorial plane. For simplicity, Figure 1 Only a portion of the tire is shown, the remaining portions not shown are identical and are arranged symmetrically with respect to the equatorial plane "XX".

[0259] The tyre 100 for four-wheel wheels comprises at least one carcass structure comprising at least one carcass ply 101 presenting mutually opposite end edges bonded to respective annular anchoring structures 102 , called bead cores, optionally associated with filler beads 104 .

[0260] The area of ​​the tire containing the bead core 102 and the bead filler 104 forms a bead structure 103 intended to anchor the tire on a corresponding mounting rim (not shown).

[0261] The carcass structure is usually of radial type, i.e. the reinforcing elements of at least one carcass layer 101 are substantially located in a plane containing the axis of rotation of the tire and substantially perpendicular to the equatorial plane of the tire. The reinforcing elements are usually represented by textile cords, such as rayon, nylon or polyester (such as polyethylene naphthalate PEN). Each bead structure is connected to the carcass structure by folding back the opposite lateral edges of at least one carcass layer 101 around annular anchoring structures 102, so as to form a so-called carcass turnup 101a.

[0262] In one embodiment, the second carcass layer ( Figure 1 ), providing a connection between the carcass structure and the bead structure.

[0263] In an outer position of each bead structure 103 there is arranged a wear strip 105 , optionally made from an elastomeric composition according to the invention.

[0264] The carcass structure is associated with a belt structure 106 comprising one or more belt layers 106a, 106b placed radially overlapping each other and the carcass layers, having typically textile or metallic reinforcing cords incorporated in a layer of vulcanized elastomeric material.

[0265] These reinforcing cords may have a crossed orientation with respect to the circumferential development direction of the tire 100. A "circumferential" direction is understood to mean a direction generally oriented in the direction of rotation of the tire.

[0266] At least one zero-degree reinforcement layer 106c, commonly referred to as a "0° belt layer", may be employed at a radially more external position relative to the belt layers 106a, 106b, which typically incorporates a plurality of elongated reinforcing elements, typically metal or textile cords, oriented in a substantially circumferential direction so as to form an angle of several degrees (e.g., an angle of about 0° to 6°) relative to a direction parallel to the equatorial plane of the tire and is coated with a vulcanized elastomeric material.

[0267] In a radially outward position with respect to the belt structure 106, a tread band 109 of vulcanized elastomeric material is applied.

[0268] Furthermore, on the lateral surfaces of the carcass structure, they each extend from one of the lateral edges of the tread 109 up to where it overlaps with the respective bead structure 103, and in a radially outward position, a respective sidewall 108 of vulcanized elastomeric material is applied.

[0269] In a radially outward position, the tread band 109 has a rolling surface 109a intended to come into contact with the ground. This surface 109a is usually provided with transverse grooves (in Figure 1 (not shown) are connected to determine the circumferential grooves of multiple small blocks of various shapes and sizes distributed on the rolling surface 109a. For simplicity, Figure 1 The word smooth is used to represent it.

[0270] A bottom layer 111 of vulcanized elastomeric material may be interposed between the belt structure 106 and the tread band 109 .

[0271] A strip 110 of elastomeric composition, generally called a “mini-sidewall” of vulcanized elastomeric material, may optionally be present in the connection zone between the sidewall 108 and the tread band 109, this mini-sidewall generally being obtained by coextrusion with the tread band 109 and allowing an improvement in the mechanical interaction between the tread band 109 and the sidewall 108. Preferably, the end portions of the sidewall 108 directly cover the lateral edges of the tread band 109.

[0272] In the case of a tubeless tire, an impermeable rubber layer 112 (commonly referred to as a "liner") required for tire inflation may also be provided at a radially inward position relative to the carcass layer 101.

[0273] The stiffness of the tire 108 may be improved in the radial direction by providing the bead structure 103 with a reinforcing layer 120 (commonly referred to as a "flipper") or additional elongated inserts.

[0274] The bead wrap 120 is a reinforcement layer that is wound around the respective bead cores 102 and filler strips 104 so as to at least partially surround them.

[0275] The flyer cover 120 typically comprises a plurality of textile cords incorporated within a layer of cured elastomeric material.

[0276] The bead structure 103 of the tyre may comprise an additional protective layer, generally known by the term “chafer” 121 or protective strip, and the function of which is to increase the rigidity and / or the integrity of the bead structure 103 .

[0277] The chafer 121 generally comprises a plurality of cords incorporated in a rubber coating of a vulcanized elastomeric material. Such cords are generally made of textile materials (such as aramid or rayon) or of metal materials (such as steel cords).

[0278] A layer or sheet of elastomeric material may be arranged between the belt structure and the carcass structure ( Figure 1 ). The layer may have a uniform thickness. Alternatively, the layer may have a variable thickness in the axial direction. For example, the layer may have a maximum thickness close to its axially outer edge relative to the central (crown) region.

[0279] Advantageously, this layer or sheet may extend over a surface substantially corresponding to the surface over which said belt structure extends.

[0280] In a preferred embodiment, a layer or sheet of elastomeric material as described above may be interposed between the belt structure and the tread band, wherein said complementary layer or sheet preferably extends on a surface substantially corresponding to the surface of extension of the belt structure.

[0281] The invention is further explained below with the aid of a number of examples, which are provided purely for illustrative purposes and do not represent any limitation of the invention.

[0282] Experimental Section

[0283] Material

[0284] All reagents and solvents were obtained from Sigma-Aldrich and used without further purification: 2,5-hexanedione (MW = 114.12 g / mol); 2-amino-1,3-propanediol (MW = 91.10 g / mol); acetone (≥ 97%); O-(2-aminopropyl)-O′-(2-methoxyethyl)polypropylene glycol (average Mn ˜600); and 2-aminoethanethiol hydrochloride (MW = 113.61 g / mol). Recorded on samples dissolved in deuterated chloroform (CDCl3) and dimethyl sulfoxide (DMSO-d6) 1 H-NMR spectrum.

[0285] The elastomers used are:

[0286] - Poly(styrene-co-butadiene) (S-SBR) from solution polymerization with anion catalysis. 25 wt% styrene, 61.7% vinyl (outside all butadiene). Mooney viscosity (ML (1+4, 100°C): 55 MU, Tg: -28°C;

[0287] - Natural origin poly(1,4-cis-isoprene), natural rubber (NR), obtained from rubber tree: STR20. From Eatern GR-Chonburi, Thailand. Mooney viscosity (ML(1+4)@100°C): 73MU. Solid natural rubber, SIR20, from Eatern GR-Chonburi, Thailand. Mooney viscosity (ML(1+4)@100°C): 73MU;

[0288] -Nitrile rubber DN 219 (NBR). From ZEON CORPORATION. Mooney viscosity (ML (1+4) @ 100℃): 22-32MU).

[0289] The carbon allotropes used are:

[0290] - Carbon black N 234 from Cabot Corporation. Carbon ≥ 98 wt%; surface area 113 m 2 / g, average size of individual particles: 27nm; average size of aggregates: 152nm;

[0291] - High surface area graphite (HSAG) Nano 27 from Asbury. Carbon ≥ 99wt%; surface area 250m 2 / g, elemental analysis (US Standard Test Sieves): carbon 99.82%, ash 0.18%, moisture 0.97%.

[0292] Ingredients used to prepare the elastomeric composition:

[0293] -ZnO (zinc oxide),

[0294] - Stearic acid (Sogis),

[0295] - 6PPD ((1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine) from Crompton,

[0296] - S (sulfur) from Solfotecnica,

[0297] - TBBS (N-tert-butyl-2-benzothiazolylsulfenamide) from Flexsys,

[0298] - CBS (N-cyclohexyl-2-benzothiazolesulfenamide) from Westco,

[0299] - TDAE (treated distilled aromatic extracted oil) Vivatec 500 (Hansen & Rosenthal KG),

[0300] - RIOWAX BM01 (wax from SER WAX INDUSTRY),

[0301] - Paraffin oil (from Sigma-Aldrich) and

[0302] - Agerite Resin D (from Vanderbilt Minerals).

[0303] Characterization

[0304] The obtained pyrrole compound was analyzed by NMR spectroscopy. A Bruker 400 MHz (100 MHz 13 C) Instruments, records 1 H-NMR and 13 C-NMR spectrum: The peak of the solvent residue was used as the internal standard, and the chemical shift was given in parts per million (ppm) (DMSO-d6: δH=2.50 ppm, CDCl3: δH=7.26 ppm).

[0305] The adducts between carbon allotropes and pyrrole compounds were characterized by the following techniques.

[0306] Thermogravimetric analysis (TGA) is a quantitative analysis technique that provides the weight loss of a material analyzed as a function of time and temperature. In other words, a material is heated using a given heating scheme, and it may undergo changes that cause a portion or all of the material itself to lose (entering the vapor phase). According to standard method ISO9924-1, under N2 flow (60mL / min), using Mettler TGA SDTA / 851 instrument, TGA is performed. Samples (10 mg) are heated from 30°C to 300°C at 10°C / min, maintained at 300°C for 10 minutes, and immediately heated to 550°C (20°C / min) thereafter. After keeping them at 550°C for 15 minutes, they are further heated to 650°C at a rate of 30°C / min and maintained at 650°C for 20min under air flow (60mL / min).

[0307] The functionalization yield of the resulting adduct was calculated using the following equation: 2 The percentage of molecules by weight that are hybridized to carbon allotropes:

[0308]

[0309] The values ​​stated for calculation purposes relate to the amount of pyrrole compound contained in the adduct before and after the purification process, determined by TGA, and to the weight loss in % determined from the TGA diagram in the temperature range running from 0 to 900° C.

[0310] The elastomeric compositions were vulcanized and characterized by the following procedures and techniques.

[0311] Crosslinking was performed using a Monsanto RPA 2000 rheometer at 170°C, using a frequency of 1.667 Hz and an angle of 6.98% (0.5 rad) for 20 and 10 min.

[0312] According to standard ISO 37:2005, at 23°C, the static mechanical properties are measured. In particular, at different elongation levels of 50%, 100% and 300%, the elongation in the order σ 50 , σ 100 , σ 300 The named loads, and in the order σ B and ε B Nominal breaking load and elongation at break. Tensile tests are performed on dumbbell-type specimens with straight axes.

[0313] The dynamic mechanical properties are measured by applying dynamic stresses at constant frequency and at constant temperature by means of shear stress, increasing the amplitude of deformation. The test is carried out using a Monsanto RPA 2000 rheometer. In the rheometer, the sample of the elastomeric material composition is kept at 50° C. for 90 seconds and then the stress is applied at 50° C., with a frequency of 1 Hz, increasing the amplitude of deformation within the range described above, within the range of deformation amplitude from 0.1% to 25%. This treatment is carried out in order to eliminate the "prior thermomechanical history". Vulcanization is then carried out at 170° C. for 20 minutes, using a frequency of 1.667 Hz and an angle of 6.98% (0.5 rad). The vulcanized sample is left at 50° C. in the instrument for 10 minutes. A sinusoidal stress is then applied at 50° C., using the same conditions already described. Then, a sinusoidal stress is applied again, always using the same experimental conditions. A curve is then obtained, which describes the modulus value as a function of the amplitude of deformation. This modulus is explained below. The G′ modulus is the elastic modulus. The G" modulus is the viscous modulus. The ratio of G" / G' is described as tanδ. From the strain sweep test, the following parameter values ​​were obtained: G'γ=0.28%, which is the G' value at the minimum deformation; △G', which is the difference between the G' value at the minimum deformation and the G' value measured at the maximum deformation achieved; G" max , which is the maximum G" value observed in the G" curve; and (tanδ) max , which is the maximum tan δ value observed in this curve.

[0314] The dynamic mechanical properties are further measured by applying axial stress in compression-traction mode using an Instron dynamic device according to the following method. The crude elastomeric composition sample, vulcanized at 170°C for 10 minutes, has a cylindrical shape (length = 25 mm; diameter = 14 mm), compression-preloaded to a maximum of 25% of the longitudinal deformation relative to the starting length and maintained at a predetermined temperature (equal to -10°C, 0°C, +23°C or +70°C) for the entire test time, and the sample is subjected to sinusoidal dynamic stretching with a frequency of 10 Hz, the sinusoidal dynamic stretching having an amplitude of ±3.5% relative to the length under preload. The dynamic mechanical properties are expressed in the form of dynamic modulus of elasticity (E') and tan δ value (dissipation factor). The tan δ value is calculated as the ratio of the viscous modulus (E") and the elastic modulus (E').

[0315] The measured static and dynamic mechanical properties are summarized in Table 1 below.

[0316] Table 1

[0317]

[0318] Example

[0319] Examples 1-3: Synthesis of Comparative Pyrrole Compounds and Those of the Invention

[0320] Example 1. Synthesis of 2-(2,5-dimethyl-1H-pyrrolo-1-yl)propane-1,3-diol (serinol pyrrole, SP), contrast

[0321]

[0322] The synthesis was carried out as described in EP3209604B1 with a reaction yield of 96%.

[0323] Example 2. Synthesis of O-(2-(2,5-dimethyl-1H-pyrrol-1-yl)propyl)-O′-(2-methoxyethyl)polypropylene Diol (PPGP), vs.

[0324]

[0325] 13.27 g of O-(2-aminopropyl)-O'-(2-methoxyethyl)polypropylene glycol (PPGA, 0.02212 mol), 2 g of 2,5-hexanedione (HD, 0.02212 mol) and 0.2 mL of water were poured into a 100 ml round-bottom flask equipped with a magnetic stirrer. The mixture was then stirred (300 rpm) at ambient temperature for 12 hours. At the end of the reaction, the mixture still contained 2,5-hexanedione. Using a Claisen apparatus, the reagent was removed under reduced pressure (2 mbar, ambient temperature). The pure product was obtained in a yield of 64%.

[0326] 1H NMR (CDCl3, 400MHz); δ (ppm) = 1.13-1.15 (m, 74H); 1.47 (d, 3H); 2.25 (s, 6H); 3.32 (m, 4H); 3 .32(m,4H);3.42-3.78(m,34H);3.66-3.5(m,55H);3.74(m,3H);4.35(quintuple,1H);5.71(s,2H).

[0327] Example 3. Synthesis of 2-(2,5-dimethyl-1H-pyrrol-1-yl)ethane-1-thiol (SHP), the present invention

[0328]

[0329] Under a constant N2 flow, 2.93 g (0.02577 mol) of 2-aminoethanethiol hydrochloride were introduced into a 50 ml round-bottom two-necked flask previously dried in an oven, and the system was brought to a maximum of 50°C under stirring (300 rpm) until complete dissolution.

[0330] The mixture was then returned to ambient temperature and 2.93 g (0.02577 mol) of 2,5-hexanedione was injected into the flask under a stream of N2. The mixture was left standing for 12 hours at ambient temperature under stirring (300 rpm). Next, 1.5 g of 2-aminoethanethiol hydrochloride was added, the temperature was brought to a maximum of 50°C, and the mixture was left under stirring for 1 hour.

[0331] The pure product was obtained by washing with water (3 x 10 mL). 3.1 g of product was obtained (yield = 77.5%).

[0332] 1 H NMR (D2O, 400MHz); δ (ppm) = 2.05 (s, 6H); 2.9 (m, 4H); 3.33 (t, 1H); 3.43 (t, 1H); 5.42 (s, 2H).

[0333] Examples 4-8: Preparation of comparative adducts between carbon allotropes and pyrrole derivatives and methods according to the invention Those adducts

[0334] Example 4. Preparation of carbon allotrope CB N234 and serinol pyrrole (CBN234-SP adduct), comparison

[0335] 10 g of carbon allotrope was placed in a 250 ml round bottom flask and 50 mL of acetone was added so as to completely cover the black powder of the allotrope. Next, 1 g of SP was dissolved in 15 mL of acetone and added to the flask. The suspension was sonicated for 10 minutes using a 2 L ultrasonic bath. The solvent was removed under reduced pressure using a rotary evaporator. The flask was then equipped with a magnetic stirrer and a condenser and heated to 180° C. in an oil bath; it was then placed under stirring (300 rpm) for 3 hours. The reaction was thus carried out without solvent or catalyst.

[0336] Once the reaction is complete, the mixture is carefully washed with acetone, left to stand overnight with stirring at ambient temperature, then placed in a Büchner funnel with a sintered glass disc, recovered and dried in an oven at 95 °C.

[0337] The adducts were characterized by TGA. The weight losses determined in the ranges T < 150 °C, 150 °C < T < 900 °C, and T ≥ 900 °C are described in Table 1. The amounts by weight of SP in the adducts, expressed both as % and as phc (relative to 100 parts of carbon), i.e., the number of parts of the compound relative to 100 parts of carbon allotropes, and the functionalization yield values are described in Table 2.

[0338] Example 5. Preparation of carbon allotropes CB N234 and PPGP (CBN234-PPGP adduct), comparison

[0339] The procedure of Example 4 was repeated using PPGP instead of SP.

[0340] The resulting CBN234-PPGP adduct was characterized by TGA. The weight losses from the TGA are described in Table 2. In Table 3, the amounts by weight of PPGP in the adduct, expressed both as % and phc, and the functionalization yield values are described.

[0341] Example 6. Preparation of carbon allotropes CB N234 and SHP (CB N234-SHP adduct), the present invention

[0342] The procedure of Example 4 was repeated using SHP instead of SP, and ethanol instead of acetone. Once the reaction is complete, the mixture is carefully washed with acetone and left to stand overnight with stirring at ambient temperature. Then it is placed in a Büchner funnel with a sintered glass disc, recovered and dried in a cabinet at ambient temperature overnight.

[0343] The resulting CBN234-SHP adduct was characterized by TGA. The weight losses from the TGA are shown in Table 2. In Table 3, the amounts by weight of SHP in the adduct, expressed both as % and phc, and the functionalization yield are shown.

[0344] Example 7. Preparation of carbon allotropes HSAG and PPGP (HSAG-PPGP adduct), comparison

[0345] The procedure of Example 5 was repeated using HSAG Nano27 instead of CB N234.

[0346] The resulting HSAG-PPGP adduct was characterized by TGA. The weight losses from the TGA are shown in Table 2. In Table 3, the amounts by weight of PPGP in the adduct, expressed both as % and phc, and the functionalization yield are shown.

[0347] Example 8. Preparation of carbon allotropes HSAG and SHP (HSAG-SHP adduct), the present invention

[0348] The procedure of Example 6 was repeated using HSAG Nano 27 instead of CBN 234.

[0349] The resulting HSAG-SHP adducts were characterized by TGA. The weight losses from TGA are shown in Table 2. In Table 3, the amount by weight of SHP in the adducts, expressed in both % and phc, and the functionalization yield of the adducts are shown.

[0350] Table 2

[0351]

[0352] Table 3

[0353]

[0354] 1 phc (relative to 100 parts of carbon) = relative to 100 parts of sp 2 Carbon allotrope, number of functionalizing agents

[0355] Examples 9-13: Preparation of Elastomer Mixtures Containing S-SBR and NR

[0356] An elastomer mixture is prepared, comprising the elastomers S-SBR and NR, and carbon black or a mixture of carbon black and one of the adducts between carbon black and an azole compound described in the previous examples.

[0357] Table 4 below shows the compositions obtained in Examples 9-13.

[0358] From the data shown in the table, it can be seen that all the compositions obtained contain a considerable amount of carbon black; the control compositions 10-12 containing a mixture of CB and an adduct contain a considerable amount of azole compound, which is approximately doubled compared to the composition (13) of the present invention; the ratio of carbon black to adduct in compositions 10 and 12 (control) is about 0.9, while in compositions 11 (control) and 13 (invention) it is about 0.5.

[0359] Table 4

[0360]

[0361] *Comparison; ^According to the present invention

[0362] Example 9. Preparation of an elastomer composition containing S-SBR, NR and CB (comparison).

[0363] S-SBR and NR were fed into an internal mixer. 65 phr of CB and oil (TDAE oil, Vivatec 500) were then added. After further kneading for 3 minutes, stearic acid, 6PPD and zinc oxide were added and the composition was kneaded for another 3 minutes before discharging it. The chamber was cooled to 45°C, the composition was fed into the mixer again, and TBBS and sulfur were added, followed by kneading for 3 minutes. The composition was then discharged. The process was carried out to fill 85% of the chamber.

[0364] Example 10. Preparation of an elastomer composition containing S-SBR, NR and CBN234-PPGP, and comparison

[0365] The procedure of Example 9 was repeated using 32.5 phr of CB and 34.5 phr of CBN234-PPGP instead of 65 phr of CB.

[0366] Example 11. Preparation of an elastomer composition containing S-SBR, NR and CBN234-SP, and comparison

[0367] The procedure of Example 9 was repeated using 43.6 phr of CB and 22.7 phr of CBN234-SP instead of 65 phr of CB.

[0368] Example 12. Preparation of an elastomer composition containing S-SBR, NR and CBN234-SP, and comparison

[0369] The procedure of Example 9 was repeated using 32.5 phr of CB and 34.3 phr of CBN234-SP instead of 65 phr of CB.

[0370] Example 13. Preparation of an elastomer composition containing S-SBR, NR and CBN234-SHP, the present invention

[0371] The procedure of Example 9 was repeated using 43.6 phr of CB and 22.4 phr of CBN234-SHP instead of 65 phr of CB. In addition, the temperature of the mixing chamber was maintained at 45° C. for the entire process.

[0372] vulcanization

[0373] According to the operation described above, at 170 °C and 15 × 10 5 The compositions of Examples 9 to 13 were vulcanized at a pressure of 1.25 Pa for 20 minutes.

[0374] In Table 5, data related to the sulfurization reaction are shown. Figure 2 In FIG. 1 , the vulcanization curve is shown.

[0375] It is particularly noteworthy that the use of the adducts according to the invention leads to a decrease in the vulcanization induction time compared to compositions containing carbon black alone, especially when the adduct CBN234-SHP is used. In any case, this value is compatible with industrial practice and can be correlated with typical values ​​obtained using vulcanization retarders.

[0376] Table 5

[0377]

[0378] *Comparison; ^According to the present invention

[0379] M H The maximum torque, measured in dNewton × meter (dNm).

[0380] M L Minimum torque value, measured in dNm.

[0381] ts1: The time required for the torque value to increase by 1 dNm, relative to the minimum value M L .

[0382] t s2 : The time required for the torque value to increase by 2dNm, relative to the minimum value M L .

[0383] t 90 : The time required to reach 90% of the torque value, relative to the maximum value M H .

[0384] All functionalized CBs resulted in an increase in the vulcanization rate, as measured by (M H -M L ) / (t 90 -t S1 ) form. Significantly higher values ​​were obtained with CBN234-SHP. No significant vulcanization reversal was observed for any of the compositions. The highest M H and M H -M L value.

[0385] Dynamic Mechanical Characterization of Elastomer Compositions Using Shear Stress

[0386] According to the previously described mode of operation, dynamic mechanical characterization was performed by applying sinusoidal stress with the aid of shear stress.

[0387] Table 6 shows data concerning the dynamic modulus G′ at the minimum deformation (0.1), the G′ modulus change (ΔG′) between 0.28% and 25% as the deformation amplitude, the maximum value of the dissipation modulus G″, and the maximum value of tan δ.

[0388] exist Figure 3 and Figure 4 The variation curves of G′ and tanδ with respect to the deformation amplitude are shown in FIG.

[0389] Table 6

[0390]

[0391] *Comparison; ^According to the present invention

[0392] The composition with CBN234-SHP shows the highest elastic modulus G′ values ​​at all deformations, and comparable G″max values.

[0393] The composition with CBN234-SHP further shows the lowest tan δ at low to high deformations max values ​​and lower tanδ values.

[0394] At the highest deformation examined, the tan δ value of composition (13) containing CBN234-SHP is similar to that of composition 12 which contains a larger amount of CBN234-SP adduct than composition 13 (34.3 phr compared to 22.4 phr, about 1.5:1).

[0395] Thus, the composition 13 of the present invention is characterized by the lowest hysteresis and the lowest energy dissipation.

[0396] Dynamic Mechanical Characterization of Elastomer Compositions by Axial Stress

[0397] The data obtained from the dynamic mechanical test by applying a sinusoidal axial stress are shown in Table 7. The experimental conditions for carrying out this test have been described above. It should be emphasized that the sinusoidal stress was applied on the sample compressed at 25%.

[0398] Table 7

[0399] Composition 9* 10* 12* 13^ Carbon allotropes CB CBN234-PPGP CBN234-SP CBN234-SHP E′@10℃ 17.52 16.51 18.28 19.92 E"@10℃ 9.74 9.73 10.19 10.13 tanδ@10℃ 0.56 0.59 0.56 0.51 E′@23℃ 13.18 12.86 14.10 15.28 E"@23℃ 6.02 6.15 6.47 6.36 tanδ@23℃ 0.46 0.48 0.46 0.42 E′@70℃ 8.18 8.09 8.40 9.12 E"@70℃ 2.06 2.19 2.17 2.03 tanδ@70℃ 0.25 0.27 0.26 0.22 ΔE′(E′@10℃-E′@70℃) 9.34 8.42 9.88 10.8

[0400] *Comparison; ^According to the present invention

[0401] The composition containing CBN234-SHP has the highest E' value at all temperatures. The increase in the E' value is greater than the increase in the E" value at all temperatures. Indeed, the composition containing CBN234-SHP has the lowest tan δ value, i.e. hysteresis, at all temperatures. Figure 5 The temperature dependence of the tan δ value is shown in FIG.

[0402] Therefore, although for the compositions with CBN234-SP and with CBN234-SHP, in Table 6 and especially Figure 4 The data for the curves in Table 7 and Table 8 show similar tan δ values ​​at high deformations, but Figure 5 The data in clearly show that after application of a preload, the composition containing only CBN234-SHP shows a significant decrease in hysteresis compared to the composition containing CB alone.

[0403] Characterization of Elastomer Compositions by Tensile Testing

[0404] In Table 8, the data obtained from the tensile tests are shown. Figure 6 , a curve showing the change in stress relative to elongation is shown.

[0405] Table 8

[0406]

[0407] *Comparison; ^According to the present invention

[0408] All compositions with functionalized CB have better fracture properties values ​​compared to compositions with non-functionalized CB. It should be emphasized that compositions with CBN234-SHP have better fracture properties compared to compositions with CB alone, but at much higher load values ​​at lower deformations of 50%, 100% and 300% compared to all other mixtures. Therefore, compositions with CBN234-SHP, which have greater stiffness and less hysteresis, also have better fracture properties than compositions with non-functionalized CB when compared to compositions with CB and to all other mixtures.

[0409] All the data collected for compositions containing S-SBR and NR demonstrate that the inventive composition (13) has the best balance of all properties: greater dynamic stiffness, less hysteresis, higher load at low deformation, and best breaking properties.

[0410] Examples 14-17. Preparation of Elastomer Compositions Containing NBR and NR

[0411] An elastomeric mixture was prepared comprising the elastomers NBR and NR and carbon black, a mixture between carbon black / high surface area graphite, or a mixture of carbon black with one of the adducts between HSAG and pyrrole compounds described in the previous examples.

[0412] Table 9 below shows the composition of the compositions obtained in Examples 14 to 17. Table 10 lists the amounts of functional groups present in the compositions.

[0413] According to the data shown in the table, it can be seen that the control composition 14 contains double the amount of carbon black compared to the others, wherein about 50% of the carbon black is replaced by HSAG (15, control) or by the adduct between HSAG and the azole compound (16, control, and 17, present invention). In addition, both compositions containing the adduct between HSAG and the azole compound contain a considerable amount of the azole compound.

[0414] Table 9

[0415] Example 14* 15* 16* 17^ Carbon allotropes CB CB / HSAG CB / HSAG-PPGP CB / HSAG-SHP [phr] [phr] [phr] [phr] NBR 70 70 70 70 NR(SIR-20) 30 30 30 30 PPGP 4 4 4 4 CB 60 30 30 30 HSAG 30 HSAG-PPGP 31.6 HSAG-SHP 31.6 Stearic acid 2 2 2 2 ZnO 5 5 5 5 Agerite Resin D 1 1 1 1 CBS 1.5 1.5 1.5 1.5 sulfur 1.5 1.5 1.5 1.5

[0416] *Comparison; ^According to the present invention

[0417] Table 10

[0418]

[0419] *Comparison; ^According to the present invention

[0420] Example 14. Preparation of an elastomer composition containing NBR, NR and CB, Comparative Example

[0421] NBR and NR are fed into an internal mixer. , and knead at 85°C for 1 minute. Then add the paraffin oil. After further kneading for 3 minutes, add stearic acid, Agerite resin D and zinc oxide, and knead the composition for another 3 minutes before discharging it. Cool the chamber to 45°C, and feed the composition into the mixer again, and add CBS and sulfur, followed by kneading for 3 minutes. Then discharge the composition. This process is carried out to fill 85% of the chamber.

[0422] Example 15. Preparation of an elastomer composition containing NBR, NR, CB and HSAG, Comparative Example

[0423] The procedure of Example 14 was repeated using a CB / HSAG mixture (50 / 50 by weight) instead of CB.

[0424] Example 16. Preparation of an elastomer composition containing NBR, NR, CB and HSAG-PPGP, Comparative Example

[0425] The procedure of Example 14 was repeated using a mixture of CB and adduct HSAG-PPGP (CB / HSAG ratio = 50 / 50 by weight) instead of CB.

[0426] Example 17. Preparation of an elastomeric composition containing NBR, NR, CB and HSAG-SHP, an embodiment of the present invention

[0427] The procedure of Example 14 was repeated using a mixture of CB and adduct HSAG-SHP (CB / HSAG ratio = 50 / 50 by weight) instead of CB. Further, the chamber temperature was maintained at 45° C. for the entire process.

[0428] Vulcanized elastomer composition

[0429] According to the operation described above, at 170 °C and 15 × 10 5 The compositions of Examples 14-17 were vulcanized at a pressure of 1.25 Pa for 20 minutes.

[0430] In Table 11, the data of the sulfurization reaction are shown. Figure 7 In FIG. 1 , the vulcanization curve is shown.

[0431] Table 11

[0432]

[0433] *Comparison; ^According to the present invention

[0434] Substituting CB with HSAG and HSAG-PPGP results in an increase in the cure induction time and a decrease in the cure rate, which is Figure 7 In contrast, with the adduct HSAG-SHP, the same vulcanization behavior observed for composition 14 containing CB alone is obtained.

[0435] In the case of compositions with HSAG as is or functionalized, M L The lowest value was obtained using HSAG-SHP.

[0436] The adducts according to the invention therefore impart advantageous properties to the elastomeric mixture, even when carbon allotropes other than CB are used.

[0437] Dynamic mechanical characterization of elastomeric compositions using shear stress

[0438] According to the operation mode described above, sinusoidal stress is applied with the help of shear stress for dynamic mechanical characterization.

[0439] Table 12 shows data concerning the dynamic modulus G′ at the minimum deformation (0.1%), the G′ modulus change Δ (ΔG′) between 0.28% and 25% as the deformation amplitude, the maximum value of the dissipation modulus G″, and the maximum value of tan δ.

[0440] Figure 8 The curve showing the change in tan δ with respect to the deformation amplitude is shown.

[0441] Table 12

[0442] Composition 14* 15* 16* 17^ Carbon allotropes CB CB / HSAG CB / HSAG-PPGP CB / HSAG-SHP <![CDATA[G′ min ]]> 8.72 5.49 5.23 5.27 <![CDATA[G′ max ]]> 1.78 1.44 1.35 1.54 △G′ 6.94 4.06 3.89 3.73 <![CDATA[G" max ]]> 1.29 0.82 0.81 0.77 <![CDATA[tanδ max ]]> 0.34 0.30 0.31 0.27

[0443] *Comparison; ^According to the present invention

[0444] The G' values ​​of the compositions containing HSAG as is or functionalized are lower than the G' values ​​of the compositions containing CB alone.

[0445] The composition containing HSAG-SHP shows the lowest value of G' at the lowest deformation, and the highest value of G' at high strain among the compositions containing HSAG.

[0446] These are positive data as they indicate that HSAG-SHP causes minimal Payne effect. Indeed, the ΔG' values ​​are significantly lower for the compositions containing HSAG-SHP.

[0447] The compositions containing HSAG-SHP also had lower G"max values.

[0448] Finally, the composition containing HSAG-SHP has the lowest tan δ value over the entire deformation range, which can be seen in Figure 8 This means that the composition containing HSAG-SHP has the smallest hysteresis and therefore the smallest energy dissipation.

[0449] Dynamic mechanical characterization of elastomeric compositions using axial stress

[0450] The data obtained from the dynamic mechanical tests carried out with sinusoidal axial stress are shown in Table 13. The experimental conditions for carrying out this test are described above. It should be emphasized that the sinusoidal stress was applied to the samples compressed at 25%.

[0451] Table 13

[0452] Composition 14* 15* 16* 17^ Carbon allotropes CB CB / HSAG CB / HSAG-PPGP CB / HSAG-SHP E′@10℃ 27.15 27.84 27.28 28.93 E"@10℃ 12.33 11.69 11.75 12.34 tanδ@10℃ 0.45 0.42 0.43 0.43 E′@23℃ 22.51 22.86 22.29 23.75 E"@23℃ 8.66 7.82 7.80 8.14 tanδ@23℃ 0.39 0.34 0.35 0.34 E′@70℃ 12.70 13.78 13.28 14.55 E"@70℃ 3.73 3.46 3.46 3.40 tanδ@70℃ 0.29 0.25 0.26 0.23 △E′(E′@10℃-E′@70℃) 14.44 14.06 14.01 14.38

[0453] *Comparison; ^According to the present invention

[0454] The composition of the present invention containing HSAG-SHP exhibits the highest E' values ​​at all temperatures, and therefore greater dynamic stiffness. This composition also exhibits lower tan delta values ​​at all temperatures than those containing CB alone, and at low temperatures is consistent with the values ​​of the compositions containing HSAG and HSAG-PPGP.

[0455] For the composition containing HSAG-SHP, the tan delta value is lowest at medium-high temperatures (70° C.) This data is certainly positive since tan delta at medium-high temperatures is an indication of the energy dissipation of a composition for a tire under normal use conditions.

[0456] Characterization of Elastomer Compositions by Tensile Testing

[0457] Table 14 shows the data obtained in the tensile tests.

[0458] Table 14

[0459] Composition 14* 15* 16* 17^ Carbon allotropes CB CB / HSAG CB / HSAG-PPGP CB / HSAG-SHP <![CDATA[σ 50 (MPa)]]> 3.59 5.17 4.38 6.71 <![CDATA[σ 200 (MPa)]]> 8.32 9.45 8.09 12.83 <![CDATA[σ 300 (MPa)]]> 14.34 13.32 11.63 17.65 <![CDATA[σ 300 / s 200 ]]> 1.72 1.41 1.44 1.38 <![CDATA[σ B (MPa)]]> 19.82 19.18 18.44 19.69 <![CDATA[ε B (%)]]> 406.94 489.53 523.93 351.48 <![CDATA[Energy (J / cm 3 )]]> 37.79 52.93 52.89 38.53

[0460] *Comparison; ^According to the present invention

[0461] The composition containing HSAG-SHP clearly shows the highest reinforcement values ​​up to 300% elongation. In addition, it shows consistent or higher break load and break energy values ​​when compared to the composition containing CB alone.

[0462] In conclusion, the composition containing the hybrid filler system CB / HSAG-SHP shows the lowest hysteresis, that is to say the lowest energy dissipation, especially under normal use conditions of the tire, and at the same time has vulcanization and static reinforcement parameters consistent with those of the reference composition containing CB alone.

Claims

1. A sp 2 An adduct between a hybridized carbon allotrope and a pyrrole derivative, wherein the pyrrole derivative is represented by formula (1a): in R1, R2, R3 and R4 are independently selected from: hydrogen, straight or branched C1-C 22 Alkyl, straight chain or branched C2-C 22 alkenyl or alkynyl; W and Y are independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, straight chain or branched C2-C 18 alkenyl or alkynyl; and Z is represented by formula (II) or formula (III) described below Among them, R5, R6, R7, R8, R9, R 10 , R 11 , R 12 and R 13 Independently selected from: hydrogen, straight or branched C1-C 18 Alkyl, straight chain or branched C2-C 18 alkenyl or alkynyl; or R7 is selected from: a linear or branched C1-C 18 Alkyl acyl-alkyl, having a straight or branched C2-C 18 acyl-alkenyl of alkenyl; or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups; and wherein m is an integer from 1 to 4, and n, o and p are independently integers from 1 to 12, Wherein the sp 2 The hybrid carbon allotrope is selected from the group consisting of carbon black, high surface area graphite, carbon nanotubes, and mixtures thereof.

2. The adduct according to claim 1, wherein the sp 2 The hybrid carbon allotrope is carbon black or high surface area graphite or a mixture thereof.

3. The adduct according to any one of claims 1 to 2, wherein the pyrrole derivative is represented by formula (1a): in R1, R2, R3 and R4 are independently selected from: hydrogen and straight or branched C1-C3 alkyl; W and Y are independently selected from: hydrogen and straight or branched C1-C3 alkyl; and Z is represented by the formula (II) or formula (III) described below Among them, R5, R6, R8, R9, R 10 and R 11 represented by hydrogen or a straight or branched C1-C3 alkyl group; and R7, R 12 and R 13 Independently selected from: hydrogen, straight or branched C1-C 18 alkyl; or R 12 and R 13 together form a pyrrole ring optionally substituted with one or more C1-C3 alkyl groups; and wherein m is 1, and n, o, p are integers from 1 to 4 independently of each other.

4. A method for preparing the adduct according to any one of claims 1 to 3, comprising the following steps: a) forming at least one compound of formula (1a) described above and at least one sp 2 mixtures of hybridized carbon allotropes; and b) supplying energy to the mixture obtained in step a) so as to obtain an adduct, c) optionally isolating the adduct obtained.

5. The preparation method according to claim 4, wherein the energy provided in step b) is selected from mechanical energy, thermal energy, and energy by irradiation with photons, or a combination thereof.

6. The preparation method according to claim 4, comprising the steps of: i) obtaining a solution of at least one compound of formula (1a) in a solvent selected from the group consisting of water, alcohols, carbonyl solvents, esters, dimethyl sulfoxide, acetonitrile, ethers or mixtures thereof; ii) obtaining a suspension of the carbon allotrope in the solvent used to prepare the solution in step i); iii) mixing the solution and the suspension by mechanical or magnetic stirring or by ultrasonic treatment; iv) removing the solvent from the mixture obtained in step iii); and v) providing thermal energy and / or mechanical energy and / or energy of irradiation with photons to the mixture obtained in step iv) in the presence of air or oxygen.

7. Use of the adduct according to any one of claims 1 to 3 for preparing a composition.

8. Use according to claim 7, wherein the composition is an elastomeric composition.

9. A crosslinkable elastomeric composition comprising the sp according to any one of claims 1 to 3 2 Adducts between hybridized carbon allotropes and pyrrole derivatives.

10. The crosslinkable elastomeric composition according to claim 9, comprising the adduct in an amount ranging from 5 to 100 phr.

11. The crosslinkable elastomeric composition according to claim 10, wherein the amount of said adduct is from 10 to 80 phr.

12. The crosslinkable elastomeric composition according to any one of claims 9 to 11, further comprising an additional reinforcing filler selected from carbon black, silica, layered silicates, mixed oxides of aluminium and magnesium having a layered structure, alumina and aluminosilicates.

13. Tyre for vehicle wheels comprising at least one structural element comprising a crosslinked elastomeric material obtained by crosslinking a crosslinkable elastomeric composition according to any one of claims 9 to 12.

14. Tyre according to claim 13, wherein said structural element is chosen from a tread band, a sidewall, a sidewall insert, a layer of elastomeric material radially internal with respect to said tread band.

15. The tire of claim 14, wherein the radially inner layer of elastomeric material is selected from cushioning and micro sidewalls, bead structures, and rubber coatings of textiles and metals.